Effects of electrode materials on the device performances and instabilities in amorphous InGaZnO thin film transistors. (September 2019) - Choi, Jong Won; Park, Sang Hyuk; Yu, Chong Gun; Cho, Won-Ju; Park, Jong Tae
Abstract: The effects of electrode materials on the device performances and instabilities in amorphous InGaZnO thin film transistors (a-IGZO TFTs) have been investigated. The dependences of the source and drain resistance (RSD ) and the effective channel length (Leff ) on the gate biases were explained by the accumulation layer under the gate overlap (LGOV ) which was formed due to the oxygen out diffusion from the channel layer. The RSD with electrode materials is determined by not only workfunction (ΦM ) but the electrical property of the metal oxide formation. From the threshold voltage shifts with different electrode materials under positive gate bias stress (PBS), the more device degradation could occur when the more electrons are accumulated in LGOV . Highlights: Effect of electrode materials on device instabilities in a-IGZO TFTs Investigate the correlation between S/D series resistance and the effective channel length with S/D electrode materials Investigate the correlation between device degradation and the effective channel length with S/D electrode materials